Sintomas do câncer infantil à luz da linguagem: uma análise de legibilidade e acessibilidade terminológica no Guia Beaba - Araujo, Alexandre Neiva de (2023)
Cancer, in addition to being a chronic disease that threatens life, is a disease that symbolizes suffering. Thus, as every disease generates instability in family dynamics, cancer, in turn, generates doubts and uncertainties regarding its discovery, treatment and control, since it is a disease with a poor prognosis, especially when related to the child, which implies a better understanding of the impact of the disease. When the person who falls ill is a child, all these emotional reactions can be more intense for the little patient (Castillo; Chesla, 2003). Childhood cancer affects all aspects of your life, as uncertainties generate stress and anxiety that are present throughout the illness until its cure. The object of study of this Master's thesis is the Beaba Cancer Guide (2021), a manual created to offer support and guidance to children facing the diagnosis of cancer. However, for the Guide to effectively fulfill its purpose, it is essential to assess the readability and textual accessibility of the terms contained therein, ensuring that the information is conveyed in an understandable manner. Taking the contribution of Terminological Textual Accessibility (Finatto, 2022; Temmerman, 2004)), Readability (Dubay, 2004, Fulgêncio; Liberato, 2007) and Legibility (Dubay, 2004), our general objective is to analyze the level of readability, readability and textual accessibility of the terms contained in the Symptoms category of the Beaba Cancer Guide (2021). The specific objectives pervade the assessment of the adequacy of technical terms, identification of the clarity of entries and investigation of the ease of use of the Guide for pediatric patients. Methodologically, after selecting the terms, we used the digital platforms Textual Legibility Analysis – ALT and Portulan Clarin to help in the process of identifying the levels of readability, readability and lexical density of the eight terms, in order to verify whether they are really understandable to the target audience of the research. When studying these terms, it was possible to perceive that it is necessary to use a simple and accessible language, making the text more understandable for child patients, as they contribute to the understanding of specific information and combat the spread of misinformation caused by lack of knowledge, leading a certain child to feel unable to inform himself, thus reducing his self-confidence during the journey. We believe that our research constitutes an important contribution to terminological studies, with regard to specialized languages ​​in the medical field. In the context of textual accessibility, information needs to be conveyed in simple language, with conditions for the public that seeks it to be used, in the case of the Guide, the child cancer patient.